ANALYSIS OF PRESSURE FLUCTUATION BEHAVIOR DURING THE RAIL GRINDING PROCESS - ZHANG KeYuan; WANG WenJian; GUO Jun; LIU QiYue (Jixie qiangdu)
There is some grinding pressure fluctuation on the rail grinding train operation,which affects the uneven surface of grinding rail. The dynamic model of rail grinding vehicle was established which gave full consideration to the grinding mechanism’s motion behavior and contact area behavior between rail and grinding wheel. Furthermore,the effect of the vertical irregularity of rail surface,grinding speed,rail corrugation and structure parameters of grinding vehicle on the grinding pressure fluctuation were explored in detail. The results show that the vertical irregularity of rail surface is the main cause of grinding pressure fluctuation. With an increase of grinding speed,the pressure fluctuation reduces. Certain wavelengths of rail corrugation result in the resonance of grinding mechanism,which causes the grinding pressure fluctuation peaks. The optimization of primary locating stiffness of grinding vehicle and the lightweight of grinding mechanism are beneficial to decrease the grinding pressure fluctuation and increase the grinding stability.